HIGH GROUNDWATER NITRATE CONCENTRATIONS INHIBIT EUTROPHICATION OF SULPHATE-RICH FRESHWATER WETLANDS - Lucassen E.C.H.E.T.; Smolders A.J.P.; van der Salm A.L.; Roelofs J.G.M. (My University, 2004)
During the last 60 years, pollution of the groundwater with NO3- has greatly increased in many parts of Europe, as a consequence of excessive use of manure and synthetic fertilisers. Monitoring of groundwater-fed wetlands indicated that sediments with high NO3- concentrations had the lowest Fe and $PO43-$ concentrations in the pore water. A comparison of two restored open water fens, differing in NO3- supply via the groundwater, indicated that the redox potential and the sulphate (SO42-) reduction rate were lower when the groundwater contained not only SO42- but also high NO3- concentrations. The lower SO42- reduction rates in the NO3- -rich open water fen were associated with lower PO43- concentrations and the presence of plant species characteristic of clear water. In contrast, the higher SO42- reduction rates in the NO3- -poor open water fen were associated with very high PO43- concentrations and massive development of plant species characteristic of eutrophic environments. Investigations at NO3- -rich seepage sites in black alder carrs, showed that high NO3- concentrations in the pore water caused chlorosis in the alder carr vegetation, due to lower availability of Fe in the pore water and less Fe uptake by the plants. Experimental desiccation of sediments proved that the NO3- -rich seepage sites contained no oxidisable FeSx, contrary to NO3- -poor locations, which became acidified and mobilised extremely high amounts of SO42- due to FeSx oxidation. A laboratory experiment showed that NO3- addition to sediments led to reduced releases of Fe, SO42- and S2-, very likely due to the oxidation of reduced Fe and S compounds. Overall, the results confirmed that NO3- is an energetically more favourable electron acceptor in anaerobic sediments than Fe and SO42-, and that high NO3- loads function as a redox buffer, preventing reduction of Fe and SO42-. Limited SO42- reduction prevents S2- -mediated mobilisation of PO43- from Fe-PO43- complexes. At a higher redox potential, reduced Fe, including FeSx, was oxidised, increasing the content of Fe(III) capable of binding PO43-. This prevented increased PO43- availability and the concomitant massive development of plant species characteristic of eutrophic environments.
Keywords: EUTROPHICATION; NITRATE; PHOSPHATE; REDOX BUFFER; SULPHATE